On School beyond Cultural Obviousness: Introduction to a Discussion - Kwaśnica, Robert (INSTED: Interdisciplinary Studies in Education & Society, 2015)
The article presents the author?s concept of the new organisation of education and a vision of school which is different from the currently binding one. The starting point for the project is the critique of the scientific and technical rationality on which the modernity of the instrumental reasoning, which is elementary in school education, was constructed. The change suggested by the writer is systemic. Its key element is the vision of a holistic school that supports pupils in their development respecting their autonomy and subjectivity. In the final part of the text the curriculum assumptions of the holistic education have been discussed as well as the organisational rules, the way of functioning and the choice of the learning contents, etc.